Consequences of maternal morbidity on health-related functioning: a systematic scoping review. Issue 6 (30th June 2017) - Machiyama, Kazuyo; Hirose, Atsumi; Cresswell, Jenny A; Barreix, Maria; Chou, Doris; Kostanjsek, Nenad; Say, Lale; Filippi, Véronique
Abstract : Objectives: To assess the scope of the published literature on the consequences of maternal morbidity on health-related functioning at the global level and identify key substantive findings as well as research and methodological gaps. Methods: We searched for articles published between 2005 and 2014 using Medline, Embase, Popline, CINAHL Plus and three regional bibliographic databases in January 2015. Design: Systematic scoping review Primary outcome: Health-related functioning Results: After screening 17 706 studies, 136 articles were identified for inclusion. While a substantial number of papers have documented mostly negative effects of morbidity on health-related functioning and well-being, the body of evidence is not spread evenly across conditions, domains or geographical regions. Over 60% of the studies focus on indirect conditions such as depression, diabetes and incontinence. Health-related functioning is often assessed by instruments designed for the general population including the 36-item Short Form or disease-specific tools. The functioning domains most frequently documented are physical and mental; studies that examined physical, mental, social, economic and specifically focused on marital, maternal and sexual functioning are rare. Only 16 studies were conducted in Africa. Conclusions: Many assessments have not been comprehensive and have paid little attention to important functioning domains for pregnant and postpartum women. The development of a comprehensive instrument specific to maternal health would greatly advance our understanding of burden of ill health associated with maternal morbidity and help set priorities. The lack of attention to consequences on functioning associated with the main direct obstetric complications is of particular concern. Review registration: CRD42015017774